Drug Transporters Polymorphism Among Indonesian Population: A Review - Adhayanti, Ida; Gafur, Abdul (Futurity Medicine, 2025)
Genetic polymorphisms in drug transporters markedly affect drug absorption, distribution, and elimination, thereby contributing to interindividual variability in pharmacological responses. A comprehensive understanding of these genetic variations is essential for the advancement of personalized medicine, especially within genetically heterogeneous populations such as Indonesia. Aims: This investigation seeks to elucidate the influence of drug transporter polymorphisms on therapeutic outcomes and their ramifications for personalized medicine in the Indonesian context. This study amalgamates existing research to furnish insights into genetic variations that impact drug metabolism, aiding the optimization of pharmacotherapy practices in Indonesia. Methodology: A systematic literature review was performed utilizing the PubMed database, identifying studies published between 2013 and 2025 that pertain to drug transporter polymorphisms within the Indonesian cohort. The data extraction process concentrated on the pharmacokinetic and pharmacodynamic implications of genetic variations in pivotal transporters. Results: A total of twelve studies were analyzed, predominantly focusing on SLC22A1, SLCO1B1, and ABCB1 polymorphisms in connection with the treatment of diabetes, cancer, epilepsy, hypercholesterolemia, and tuberculosis. The SLC22A1 Met420del variant was associated with modified metformin pharmacokinetics, while SLCO1B1 polymorphisms influenced statin metabolism, and ABCB1 variants were investigated concerning chemotherapy drug resistance. Nevertheless, inconsistent clinical significance was noted, attributable to limited sample sizes and discrepancies in methodologies. Scientific Novelty: This study underscores the imperative to incorporate pharmacogenetic principles into Indonesia's healthcare framework while addressing challenges such as research funding, restricted access to diverse samples, and lack of pharmacogenetic knowledge among practitioners. This research uniquely consolidates evidence regarding genetic determinants that influence drug metabolism in Indonesia, thereby establishing a foundational basis for personalized medicine initiatives within a genetically diverse population. Conclusion: Pharmacogenetics can optimize resources, decrease side effects, and increase treatment efficacy. Future initiatives should prioritize expanded research, public awareness, and governmental support to ensure the effective implementation of personalized medicine in Indonesia.